2007
DOI: 10.1088/1751-8113/40/43/005
|View full text |Cite
|
Sign up to set email alerts
|

Stable oscillations of a predator–prey probabilistic cellular automaton: a mean-field approach

Abstract: Abstract.We analyze a probabilistic cellular automaton describing the dynamics of coexistence of a predator-prey system. The individuals of each species are localized over the sites of a lattice and the local stochastic updating rules are inspired on the processes of the Lotka-Volterra model. Two levels of mean-field approximations are set up. The simple approximation is equivalent to an extended patch model, a simple metapopulation model with patches colonized by prey, patches colonized by predators and empty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 44 publications
(84 reference statements)
3
25
0
2
Order By: Relevance
“…In this case also, sustained oscillations have been identified in a small region of the phase diagram of the PA equations of a two parameter predator-prey model on the square lattice [15,16]. Not much is known about predator-prey interaction parameters [30], and this small oscillatory phase may correspond to biologically realistic parameter values for some predatorprey pairs.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this case also, sustained oscillations have been identified in a small region of the phase diagram of the PA equations of a two parameter predator-prey model on the square lattice [15,16]. Not much is known about predator-prey interaction parameters [30], and this small oscillatory phase may correspond to biologically realistic parameter values for some predatorprey pairs.…”
Section: Introductionmentioning
confidence: 86%
“…The performance of the PA was compared with the perfect mixing or mean field approximation (MFA) for several different population dynamics models on lattices and other graphs [14,15,16,17,18]. In these studies, the PA was found to perform much better than the MFA in the prediction of the steady state of the system, and to give a good quantitative agreement in a large region of parameter space.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropic cellular automaton is a variation of the automaton introduced in [10,14,17,18]. Here each site of a regular square lattice interacts with its first neighbors only at two preferential directions.…”
Section: Modelmentioning
confidence: 99%
“…In the last years a particular great effort has been done in order to understand the role of space given by a spatial structure and local interactions in the characterization of the dynamics of competing biological species systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In this context it has been studied irreversible stochastic lattice models [19][20][21] with the purpose of mimic predator-prey systems with Markovian local rules based in the Lotka-Volterra model [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation